(untitled) (Human Geographies – Journal of Studies and Research in Human Geography, 2025)
Time Geography is a boundary-oriented approach to understanding human activity in space and time. In this study, this concept is implemented to identify the daily activities of Women Headed Household (WHH) and their survival strategies in drought disasters and to understand their root causes through analysing capability, coupling, and authority constraints. This research starts to fill the gap in knowledge of the Time Geography in "Gender and Disaster". The combination of Time Geography’s daily diary technique with in-depth interviews is used to understand the constraining and enabling conditions in local contexts. The results show that the socio-economic characteristics of WHH in Gunung Butak Hamlet, Java, Indonesia, tended to be homogeneous and formed a pattern of daily activity with low variation. Likewise, their strategy in dealing with drought. The three geographical constraints faced by WHH in this hamlet are interrelated and do not stand alone.